2005
DOI: 10.1111/j.1742-7843.2005.pto_137.x
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant and Behavioural Effects of the Denatured Venom of the Social Wasp Polybia occidentalis (Polistinae, Vespidae)

Abstract: Several investigations demonstrate that neurotoxins isolated from venoms of spiders and wasps may exert specific and selective activity on structures of the mammalian CNS. In the present work we examine the neurological effects of the low molecular weight compounds of the denatured venom of the neotropical social wasp Polybia occidentalis in freely moving rats. Central administration of denatured venom decreased the duration of exploratory, elevation and grooming behaviours on the open field. Moreover, denatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 42 publications
1
16
0
1
Order By: Relevance
“…This effect was also found in a study with crude denatured venom of Polybia occidentalis ,[32] in which the authors observed protection from seizures induced by four distinct convulsants: bicuculline, picrotoxin, kainic acid, and PTZ, although protection against the latter was less effective. Another study[31] demonstrated similar effects of the denatured venom of Polybia ignobilis , with protection being observed from seizures induced by the same convulsants cited above, except PTZ.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…This effect was also found in a study with crude denatured venom of Polybia occidentalis ,[32] in which the authors observed protection from seizures induced by four distinct convulsants: bicuculline, picrotoxin, kainic acid, and PTZ, although protection against the latter was less effective. Another study[31] demonstrated similar effects of the denatured venom of Polybia ignobilis , with protection being observed from seizures induced by the same convulsants cited above, except PTZ.…”
Section: Discussionsupporting
confidence: 66%
“…It was observed that the different doses of LMWC-Pp significantly reduced, in a manner independent of dose, the number of lines crossed by the animals, although this effect was moderate when compared to the DZP group. Other authors have also demonstrated this effect of wasp venom on spontaneous locomotor activity, with reports suggesting it to be dependent[32] or independent[31] of the dose.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations